2015
DOI: 10.1116/1.4936072
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature sequential pulsed chemical vapor deposition of ternary BxGa1-xN and BxIn1-xN thin film alloys

Abstract: In this work, the authors have performed sequential pulsed chemical vapor deposition of ternary BxGa1-xN and BxIn1-xN alloys at a growth temperature of 450 °C. Triethylboron, triethylgallium, trimethylindium, and N2 or N2/H2 plasma have been utilized as boron, gallium, indium, and nitrogen precursors, respectively. The authors have studied the compositional dependence of structural, optical, and morphological properties of BxGa1-xN and BxIn1-xN ternary thin film alloys. Grazing incidence X-ray diffraction meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Several works on ALD and sequential CVD of BN have been published since the last fifteen years. 53,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] However, the crystalline quality, due to the mild growth temperature used, still needs improvement and post annealing is usually employed. The different ALD strategies for BN (Table 1) will be discussed according to the type of boron precursor.…”
Section: Fabrication Of Bnmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works on ALD and sequential CVD of BN have been published since the last fifteen years. 53,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] However, the crystalline quality, due to the mild growth temperature used, still needs improvement and post annealing is usually employed. The different ALD strategies for BN (Table 1) will be discussed according to the type of boron precursor.…”
Section: Fabrication Of Bnmentioning
confidence: 99%
“…These limitations might be addressed using ALD. Several works on ALD and sequential CVD of BN have been published since the last fifteen years [53,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. However, the crystalline quality, due to the mild growth temperature used, still needs improvement and post annealing is usually employed.…”
Section: Fabrication Of Bnmentioning
confidence: 99%
“…Towards this goal, we recently have demonstrated the low-temperature atomic layer deposition of ternary In x Ga 1−x N, B x Ga 1−x N, and B x In 1−x N alloys on Si substrates using a remotely integrated hollow-cathode plasma source. 23, 24 Nepal et al have reported atomic layer epitaxy (ALE) of InN thin films on sapphire, the conventional substrate material for III-nitride growth, utilizing quartz-based inductively coupled plasma source. 25 On the other hand, silicon, the material of choice for micro-electronics industry, offers cost-effective, large wafer-diameter, high-quality substrates with inherent CMOS manufacturing compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The most common precursors for ALD of InN are In(CH 3 ) 3 and N 2 plasma [154][155][156][157]. Atomic layer epitaxy of InN has been reported using In(CH 3 ) 3 and N 2 plasma as reactants and novel cubic or a hexagonal phase of InN were synthesized [158].…”
Section: Nitridesmentioning
confidence: 99%